Manajemen Kemitraan Sekolah Menengah Kejuruan Negeri (Studi Multi Situs di SMKN 3 Palangka Raya Dan SMKN 4 Banjarmasin) - Nopri Setiawan; Aslamiah Aslamiah; Ahmad Suriansyah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: Vocational education in Indonesia, particularly in Vocational High Schools, plays a crucial role in preparing competent human resources for the workplace. This study aims to describe partnership management at SMKN 3 Palangka Raya and SMKN 4 Banjarmasin. The research focuses on: 1) principal strategies; 2) teacher empowerment; and 3) partnership management. This research employed a qualitative approach, employing interview, observation, and documentation techniques. Data collected through these various techniques were examined, and data reduction, presentation, and verification were performed. Data validity was checked using credibility, transferability, dependability, and confirmability. The data were then analyzed using single-case analysis and cross-site analysis. The results of the study show regular communication partnerships with industrial partners to adjust the curriculum and teaching materials to be relevant to the needs of the large-scale job market. Synchronizing the curriculum and making PKL as the main means of providing students. Partnership with hotel kitchens through an internship teacher program, the existence of industry classes and internships for students. Partnership between SMK Negeri 3 Palangka Raya and SMK Negeri 4 Banjarmasin, an internship student program in Japan and training by trainers from Thailand. Partnership between SMK Negeri 4 Banjarmasin with hotels in Yogyakarta and an overseas internship teacher program. Teacher empowerment as an improvement and renewal of competencies according to industry trends, both through external training and internal collaboration. Teacher empowerment through internship teachers in partner hotel kitchens with guest teachers and alumni teaching. SMK Negeri 3 Palangka Raya with training from Thai trainers aims at empowerment in sister schools. SMK Negeri 4 Banjarmasin with an overseas internship teacher program and the aim of empowering teachers in alliance reference vocational schools. Principal strategies through partnership innovation and teacher empowerment in improving SMK Centers of Excellence. The principal of SMK Negeri 3 Palangka Raya focuses on strengthening the school's image through student achievement and fostering positive relationships with industry partners. SMK Negeri 4 Banjarmasin is collaborative and adaptive, actively participating in partnerships and public events to branding school promote Keywords: manajemen, kemitraan, pemberdayaan guru, strategi kepala sekolah Abstrak: Pendidikan vokasi di Indonesia pada Sekolah Menengah Kejuruan, memiliki peran yang sangat penting dalam menyiapkan sumber daya manusia yang kompeten dalam menghadapi kerja. Penelitian ini bertujuan untuk mendeskripsikan manajemen kemitraan dalam di SMKN 3 Palangka Raya dan SMKN 4 Banjarmasin. Fokus penelitian mencakup; 1) strategi kepala sekolah; 2) pemberdayaan guru; dan 3) manajemen kemitraan. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan teknik wawancara, observasi, dan dokumentasi. Data yang terkumpul melalui berbagai teknik tersebut diperiksa dan dilakukan reduksi data, penyajian data, dan verifikasi data. Pengecekan keabsahan data dilakukan dengan menggunakan kredibilitas, transferabilitas, dependabilitas dan konfirmabilitas. Kemudian data dianalisis dengan analisis kasus tunggal dan analisis lintas situs. Hasil penelitian menunjukkan Kemitraan komunikasi rutin dengan mitra industri untuk menyesuaikan kurikulum dan materi ajar agar relevan dengan kebutuhan pasar kerja skala besar. Sinkronisasi kurikulum dan menjadikan PKL sebagai sarana utama pembekalan siswa. Kemitraan dengan kitchen hotel melalui program guru magang, adanya kelas industry dan magang bagi siswa. Kemitraan SMK Negeri 3 Palangka Raya dengan SMK Negeri 4 Banjarmasin, program siswa magang di Jepang dan pelatihan oleh trainer dari Thailand. Kemitraan SMK Negeri 4 Banjarmasin dengan hotel di Yogyakarta dan program guru magang di luar negeri. Pemberdayaan guru sebagai peningkatan dan keterbaruan kompetensi sesuai tren industri, baik melalui pelatihan eksternal maupun kolaborasi internal. Pemberdayaan guru melalui guru magang di kitchen hotel mitra adanya guru tamu dan alumni mengajar. SMK Negeri 3 Palangka Raya dengan pelatihan dari trainer Thailand tujuan pemberdayaan dalam sekolah sister school. SMK Negeri 4 Banjarmasin dengan program guru magang di luar negeri dan tujuan pemberdayaan guru dalam sekolah SMK rujukan aliansi. Strategi kepala sekolah melalui inovasi kemitraan dan pemberdayaan guru dalam meningkatkan SMK Pusat Keunggulan. Kepala sekolah SMK Negeri 3 Palangka Raya fokus pada penguatan citra sekolah lewat prestasi siswa, dan menjalin hubungan baik dengan mitra industri. SMK Negeri 4 Banjarmasin dengan kolaboratif dan adaptif serta aktif dalam mitra dan event publik untuk branding sekolah rujukan. Kata kunci: management, partnership, teacher empowerment, headmaster strategy